VASYL STEFANYK’S KRAKOW - Romanowski, Andrzej (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article revolves around the «dialogue» between Vasyl Stefanyk and cultural, spiritual and literary and artistic Krakow. The purpose of the study is to figure out the role and significance of this European city in the life and work of the Ukrainian classical writer, their mutual influence and relationships. The main research methods rely on biographical and cultural-historical approaches in the analysis of the life facts and short stories of the writer. The results of the study: the author of the article views the city of Krakow as a text and an aesthetic school, which affected the work of a Ukrainian writer, the article traces a pattern of close relationships between Vasyl Stefanyk, Stanislav Przybyshevsky, Vladyslav Orkan, Vaclav Morachevsky, as well as other Ukrainian representatives of the literary and artistic center of then Krakow – Bohdan Lepkyi, Ivan Trush. Rich factual material concerning literary works of Vasyl Stefanyk convincingly proves that many of them were created in the Krakow atmosphere and environment. The scientific novelty of the article is based on the perception of Krakow as a center not only of Polish, but also of European cultures and its relationship with the life and work of the Ukrainian writer Vasyl Stefanyk. The practical significance of the article is that its material can be used in the study of the Vasyl Stefanyk literary legacy, as well as in the study of the Ukrainian-Polish literary and artistic ties.